2022
DOI: 10.3390/immuno2040040
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Derived Small Molecule AVR-48 Reprograms the Resting Macrophages to an Intermediate Phenotype and Decrease Pseudomonas aeruginosa Mouse Lung Infection

Abstract: AVR-48 is a structural derivative of chitin previously shown by our laboratory to significantly decrease lung injury parameters in LPS, hyperoxia and sepsis-induced rodent models. The current study objectives are to determine the cellular mechanism of action and demonstrate efficacy in a mouse bacterial lung infection model. For in vitro receptor binding and macrophage polarization studies, C57Bl/6J mouse derived spleens and human peripheral blood mononuclear cells (hPBMCs) were treated with AVR-48 ± LPS or bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Research has indicated that chitosan (CHS), a (1-4)-linked d-glucosamine, and chitin (CHT), a (1-4)-N-acetyl-d-glucosamine, can enhance the immune responses of broiler chickens (Menconi et al, 2014). There have been findings that CHT enhances macrophage activation and the production of inflammatory cytokines (Behera et al, 2022;Komi et al, 2018). Additional investigations found that CHS increased the nitric oxide (NO) manufacturing process, activated macrophages, increased iNOS expression and activity, and secreted more TNF, IL-1, and IL-2 in broiler chicks (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that chitosan (CHS), a (1-4)-linked d-glucosamine, and chitin (CHT), a (1-4)-N-acetyl-d-glucosamine, can enhance the immune responses of broiler chickens (Menconi et al, 2014). There have been findings that CHT enhances macrophage activation and the production of inflammatory cytokines (Behera et al, 2022;Komi et al, 2018). Additional investigations found that CHS increased the nitric oxide (NO) manufacturing process, activated macrophages, increased iNOS expression and activity, and secreted more TNF, IL-1, and IL-2 in broiler chicks (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%